You are on page 1of 8

Chapter 13 - Section B - Non-Numerical Solutions

13.1 (a) 4NH
3
(g) +5O
2
(g) →4NO(g) +6H
2
O(g)
ν =

i
ν
i
= −4 −5 +4 +6 = 1 n
0
=

i
0
= 2 +5 = 7
By Eq. (13.5),
y
NH
3
=
2 −4ε
7 +ε
y
O
2
=
5 −5ε
7 +ε
y
NO
=

7 +ε
y
H
2
O
=

7 +ε
(b) 2H
2
S(g) +3O
2
(g) →2H
2
O(g) +2SO
2
(g)
ν =

i
ν
i
= −2 −3 +2 +2 = −1 n
0
=

i
0
= 3 +5 = 8
By Eq. (13.5),
y
H
2
S
=
3 −2ε
8 −ε
y
O
2
=
5 −3ε
8 −ε
y
H
2
O
=

8 −ε
y
SO
2
=

8 −ε
(c) 6NO
2
(g) +8NH
3
(g) →7N
2
(g) +12H
2
O(g)
ν =

i
ν
i
= −6 −8 +7 +12 = 5 n
0
=

i
0
= 3 +4 +1 = 8
By Eq. (13.5),
y
NO
2
=
3 −6ε
8 +5ε
y
NH
3
=
4 −8ε
8 +5ε
y
N
2
=
1 +7ε
8 +5ε
y
H
2
O
=
12ε
8 +5ε
13.2 C
2
H
4
(g) +
1
2
O
2
(g) →(CH
2
)
2
O(g) (1)
C
2
H
4
(g) +3O
2
(g) →2CO
2
(g) +2H
2
O(g) (2)
The stoichiometric numbers ν
i, j
are as follows:
i = C
2
H
4
O
2
(CH
2
)
2
O CO
2
H
2
O
j ν
j
1 −1 −
1
2
1 0 0 −
1
2
2 −1 −3 0 2 2 0
n
0
=

i
0
= 2 +3 = 5
By Eq. (13.7),
y
C
2
H
4
=
2 −ε
1
−ε
2
5 −
1
2
ε
1
y
O
2
=
3 −
1
2
ε
1
−3ε
2
5 −
1
2
ε
1
y
(CH
2
)
2
O
=
ε
1
5 −
1
2
ε
1
y
CO
2
=

2
5 −
1
2
ε
1
y
H
2
O
=

2
5 −
1
2
ε
1
701
13.3 CO
2
(g) +3H
2
(g) →CH
3
OH(g) +H
2
O(g) (1)
CO
2
(g) +H
2
(g) →CO(g) +H
2
O(g) (2)
The stoichiometric numbers ν
i, j
are as follows:
i = CO
2
H
2
CH
3
OH CO H
2
O
j ν
j
1 −1 −3 1 0 1 −2
2 −1 −1 0 1 1 0
n
0
=

i
0
= 2 +5 +1 = 8
By Eq. (13.7),
y
CO
2
=
2 −ε
1
−ε
2
8 −2ε
1
y
H
2
=
5 −3ε
1
−ε
2
8 −2ε
1
y
CH
3
OH
=
ε
1
8 −2ε
1
y
CO
=
1 +ε
2
8 −2ε
1
y
H
2
O
=
ε
1

2
8 −2ε
1
13.7 The equation for G

, appearing just above Eq. (13.18) is:
G

= H

0

T
T
0
(H

0
−G

0
) + R
_
T
T
0
C

P
R
dT − RT
_
T
T
0
C

P
R
dT
T
To calculate values of G

, one combines this equation with Eqs. (4.19) and (13.19), and evaluates
parameters. In each case the value of H

0
= H

298
is tabulated in the solution to Pb. 4.21. In
addition, the values of A, B, C, and D are given in the solutions to Pb. 4.22. The required
values of G

0
= G

298
in J mol
−1
are:
(a) −32,900; (f ) −2,919,124; (i) 113,245; (n) 173,100; (r) −39,630; (t) 79,455; (u) 166,365;
(x) 39,430; (y) 83,010
13.8 The relation of K
y
to P and K is given by Eq. (13.28), which may be concisely written:
K
y
=
_
P
P

_
−ν
K
(a) Differentiate this equation with respect to T and combine with Eq. (13.14):
_
∂ K
y
∂T
_
P
=
_
P
P

_
−ν
dK
dT
=
K
y
K
dK
dT
= K
y
d ln K
dT
=
K
y
H

RT
2
Substitute into the given equation for (∂ε
e
/∂T)
P
:
_
∂ε
e
∂T
_
P
=
K
y
RT
2

e
dK
y
H

(b) The derivative of K
y
with respect to P is:
_
∂ K
y
∂ P
_
T
= −ν
_
P
P

_
−ν−1
1
P

K = −νK
_
P
P

_
−ν
_
P
P

_
−1
1
P

=
−νK
y
P
702
Substitute into the given equation for (∂ε
e
/∂ P)
T
:
_
∂ε
e
∂ P
_
T
=
K
y
P

e
dK
y
(−ν)
(c) With K
y


i
(y
i
)
ν
i
, ln K
y
=

i
ν
i
ln y
i
. Differentiation then yields:
1
K
y
dK
y

e
=

i
ν
i
y
i
dy
i

e
(A)
Because y
i
= n
i
/n,
dy
i

e
=
1
n
dn
i

e

n
i
n
2
dn

e
=
1
n
_
dn
i

e
− y
i
dn

e
_
But n
i
= n
i
0

i
ε
e
and n = n
0
+νε
e
Whence,
dn
i

e
= ν
i
and
dn

e
= ν
Therefore,
dy
i

e
=
ν
i
− y
i
ν
n
0
+νε
e
Substitution into Eq. (A) gives
1
K
y
dK
y

e
=

i
ν
i
y
i
_
ν
i
− y
i
ν
n
0
+νε
e
_
=
1
n
0
+νε
e

i
_
ν
2
i
y
i
−ν
i
ν
_
=
1
n
0
+νε
e
m

i =1
_
ν
2
i
y
i
−ν
i
m

k=1
ν
k
_
In this equation, both K
y
and n
0
+νε
e
(= n) are positive. It remains to show that the summation
term is positive. If m = 2, this term becomes
ν
2
1
y
1
−ν
1

1

2
) +
ν
2
2
y
2
−ν
2

1

2
) =
(y
2
ν
1
− y
1
ν
2
)
2
y
1
y
2
where the expression on the right is obtained by straight-forward algebraic manipulation. One
can proceed by induction to find the general result, which is
m

i =1
_
ν
2
i
y
i
−ν
i
m

k=1
ν
k
_
=
m

i
m

k
(y
k
ν
i
− y
i
ν
k
)
2
y
i
y
k
(i < k)
All quantities in the sum are of course positive.
13.9
1
2
N
2
(g) +
3
2
H
2
(g) →NH
3
(g)
For the given reaction, ν = −1, and for the given amounts of reactants, n
0
= 2.
By Eq. (13.5), y
N
2
=
1
2
(1 −ε
e
)
2 −ε
e
y
H
2
=
3
2
(1 −ε
e
)
2 −ε
e
y
NH
3
=
ε
e
2 −ε
e
By Eq. (13.28),
y
NH
3
y
1/2
N
2
y
3/2
H
2
=
ε
e
(2 −ε
e
)
[
1
2
(1 −ε
e
)]
1/2
[
3
2
(1 −ε
e
)]
3/2
= K
P
P

703
Whence,
ε
e
(2 −ε
e
)
(1 −ε
e
)
2
=
_
1
2
_
1/2
_
3
2
_
3/2
K
P
P

= 1.299K
P
P

This may be written: rε
e
2
−2rε
e
+(r −1) = 0
where, r ≡ 1 +1.299K
P
P

The roots of the quadratic are: ε
e
= 1 ±
1
r
1/2
= 1 ±r
−1/2
Because ε
e
< 1, ε
e
= 1 −r
−1/2
, ε
e
= 1 −
_
1 +1.299K
P
P

_
−1/2
13.10 The reactions are written:
Mary:
2NH
3
+3NO →3H
2
O +
5
2
N
2
(A)
Paul:
4NH
3
+6NO →6H
2
O +5N
2
(B)
Peter:
3H
2
O +
5
2
N
2
→2NH
3
+3NO (C)
Each applied Eqs. (13.11b) and (13.25), here written:
ln K = −G

/RT and K = (P

)
−ν

i
(
ˆ
f
i
)
ν
i
For reaction (A), G

A
= 3G

f
H
2
O
−2G

f
NH
3
−3G

f
NO
For Mary’s reaction ν =
1
2
, and:
K
A
= (P

)

1
2
ˆ
f
3
f
H
2
O
ˆ
f
5/2
f
N
2
ˆ
f
2
f
NH
3
ˆ
f
3
f
NO
and ln K
A
=
−G

A
RT
For Paul’s reaction ν = 1, and
K
B
= (P

)
−1
ˆ
f
6
f
H
2
O
ˆ
f
5
f
N
2
ˆ
f
4
f
NH
3
ˆ
f
6
f
NO
and ln K
B
=
−2G

A
RT
For Peter’s reaction ν = −
1
2
, and:
K
C
= (P

)
1
2
ˆ
f
2
f
NH
3
ˆ
f
3
f
NO
ˆ
f
3
f
H
2
O
ˆ
f
5/2
f
N
2
and ln K
C
=
G

A
RT
In each case the two equations are combined:
Mary: (P

)

1
2
ˆ
f
3
f
H
2
O
ˆ
f
5/2
f
N
2
ˆ
f
2
f
NH
3
ˆ
f
3
f
NO
= exp
−G

A
RT
704
Paul: (P

)
−1
ˆ
f
6
f
H
2
O
ˆ
f
5
f
N
2
ˆ
f
4
f
NH
3
ˆ
f
6
f
NO
=
_
exp
−G

A
RT
_
2
Taking the square root yields Mary’s equation.
Peter: (P

)
1
2
ˆ
f
2
f
NH
3
ˆ
f
3
f
NO
ˆ
f
3
f
H
2
O
ˆ
f
5/2
f
N
2
=
_
exp
−G

A
RT
_
−1
Taking the reciprocal yields Mary’s equation.
13.24 Formation reactions:
1
2
N
2
+
3
2
H
2
→NH
3
(1)
1
2
N
2
+
1
2
O
2
→NO (2)
1
2
N
2
+O
2
→NO
2
(3)
H
2
+
1
2
O
2
→H
2
O (4)
Combine Eq. (3) with Eq. (1) and with Eq. (2) to eliminate N
2
:
NO
2
+
3
2
H
2
→NH
3
+O
2
(5)
NO
2

1
2
O
2
+NO (6)
The set now comprises Eqs. (4), (5), and (6); combine Eq. (4) with Eq. (5) to eliminate H
2
:
NO
2
+
3
2
H
2
O →NH
3
+1
3
4
O
2
(7)
Equations (6) and (7) represent a set of independent reactions for which r = 2. Other equivalent sets
of two reactions may be obtained by different combination procedures. By the phase rule,
F = 2 −π + N −r −s = 2 −1 +5 −2 −0 F = 4
13.35 (a) Equation (13.28) here becomes:
y
B
y
A
=
_
P
P

_
0
K = K
Whence,
y
B
1 − y
B
= K(T)
(b) The preceding equation indicates that the equilibrium composition depends on temperature only.
However, application of the phase rule, Eq. (13.36), yields:
F = 2 +2 −1 −1 = 2
This result means in general for single-reaction equilibrium between two species A and B that
two degrees of freedom exist, and that pressure as well as temperature must be specified to fix the
equilibrium state of the system. However, here, the specification that the gases are ideal removes
the pressure dependence, which in the general case appears through the
ˆ
φ
i
s.
13.36 For the isomerization reaction in the gas phase at low pressure, assume ideal gases. Equation (13.28)
then becomes:
y
B
y
A
=
_
P
P

_
0
K = K whence
1 − y
A
y
A
= K(T)
705
Assume that vapor/liquid phase equilibrium can be represented by Raoult’s law, because of the low
pressure and the similarity of the species:
x
A
P
sat
A
(T) = y
A
P and (1 − x
A
)P
sat
B
(T) = (1 − y
A
)P
(a) Application of Eq. (13.36) yields: F = 2 −π + N −r = 2 −2 +2 −1 = 1
(b) Given T, the reaction-equilibriuum equation allows solution for y
A
. The two phase-equilibrium
equations can then be solved for x
A
and P. The equilibrium state therefore depends solely on T.
13.38 (a) For low pressure and a temperature of 500 K, the system is assumed to be a mixture of ideal
gases, for which Eq. (13.28) is appropriate. Therefore,
y
MX
y
OX
=
_
P
P

_
0
K
I
= K
I
y
PX
y
OX
=
_
P
P

_
0
K
II
= K
II
y
EB
y
OX
=
_
P
P

_
0
K
III
= K
III
(b) These equation equations lead to the following set:
y
MX
= K
I
y
OX
(1) y
PX
= K
II
y
OX
(2) y
EB
= K
III
y
OX
(3)
The mole fractions must sum to unity, and therefore:
y
OX
+ K
I
y
OX
+ K
II
y
OX
+ K
III
y
OX
= y
OX
(1 + K
I
+ K
II
+ K
III
) = 1
y
OX
=
1
1 + K
I
+ K
II
+ K
III
(4)
(c) With the assumption that C

P
= 0 and therefore that K
2
= 1, Eqs. (13.20), (13.21), and (13.22)
combine to give:
K = K
0
K
1
= exp
_
−G

298
RT
0
_
exp
_
H

298
RT
0
_
1 −
T
0
T
__
Whence, K = exp
_
_
_
_
H

298
_
1 −
298.15
500
_
−G

298
(8.314)(298.15)
_
¸
¸
_
The data provided lead to the following property changes of reaction and equilibrium constants
at 500 K:
Reaction H

298
G

298
K
I −1,750 −3,300 2.8470
II −1,040 −1,000 1.2637
III 10,920 8,690 0.1778
706
(d) Substitution of numerical values into Eqs. (1), (2), (3), and (4) yields the following values for the
mole fractions:
y
OX
= 0.1891 y
MX
= 0.5383 y
PX
= 0.2390 y
EB
= 0.0336
13.40 For the given flowrates, n
A
0
= 10 and n
B
0
= 15, with n
A
0
the limiting reactant without (II)
n
A
= n
A
0
−ε
I
−ε
II
n
B
= n
B
0
−ε
I
n
C
= ε
I
−ε
II
n
D
= ε
II
n = n
0
−ε
I
−ε
II
Use given values of Y
C
and S
C/D
to find ε
I
and ε
II
:
Y
C
=
ε
I
−ε
II
n
A
0
and S
C/D
=
ε
I
−ε
II
ε
II
Solve for ε
I
and ε
II
:
ε
I
=
_
S
C/D
+1
S
C/D
_
n
A
0
Y
C
=
_
2 +1
2
_
×10 ×0.40 = 6
ε
II
=
n
A
0
Y
C
S
C/D
=
10 ×0.40
2
= 2
n
A
= 10 −6 −2 = 2
n
B
= 15 −6 = 9
n
C
= 6 −2 = 4
n
D
= 2 = 2
n = 17
y
A
= 2/17 = 0.1176
y
B
= 9/17 = 0.5295
y
C
= 4/17 = 0.2353
y
D
= 2/17 = 0.1176
= 1
13.42 A compound with large positive G

f
has a disposition to decompose into its constituent elements.
Moreover, large positive G

f
often implies large positive H

f
. Thus, if any decomposition product
is a gas, high pressures can be generated in a closed system owing to temperature increases resulting
from exothermic decomposition.
13.44 By Eq. (13.12), G



i
ν
i
G

i
and from Eq. (6.10), (∂G

i
/∂ P)
T
= V

i
_
∂G

∂ P

_
T
=

i
ν
i
_
∂G

i
∂ P

_
T
=

i
ν
i
V

i
For the ideal-gas standard state, V

i
= RT/P

. Therefore
_
∂G

∂ P

_
T
=

i
ν
i
_
RT
P

_
=
νRT
P

and G

(P

2
) −G

(P

1
) = νRT ln
P

2
P

1
13.47 (a) For isomers at low pressure Raoult’s law should apply:
P = x
A
P
sat
A
+ x
B
P
sat
B
= P
sat
B
+ x
A
(P
sat
A
− P
sat
B
)
For the given reaction with an ideal solution in the liquid phase, Eq. (13.33) becomes:
K
l
=
x
B
x
A
=
1 − x
A
x
A
from which x
A
=
1
K
l
+1
707
The preceding equation now becomes,
P =
_
1 −
1
K
l
+1
_
P
sat
B
+
_
1
K
l
+1
_
P
sat
A
P =
_
K
l
K
l
+1
_
P
sat
B
+
_
1
K
l
+1
_
P
sat
A
(A)
For K
l
= 0 P = P
sat
A
For K
l
= ∞ P = P
sat
B
(b) Given Raoult’s law:
1 = x
A
+ x
B
= y
A
P
P
sat
A
+ y
B
P
P
sat
B
= P
_
y
A
P
sat
A
+
y
B
P
sat
B
_
P =
1
y
A
/P
sat
A
+ y
B
/P
sat
B
=
P
sat
A
P
sat
B
y
A
P
sat
B
+ y
B
P
sat
A
=
P
sat
A
P
sat
B
P
sat
A
+ y
A
(P
sat
B
− P
sat
A
)
For the given reaction with ideal gases in the vapor phase, Eq. (13.28) becomes:
y
B
y
A
= K
v
whence y
A
=
1
K
v
+1
Elimination of y
A
from the preceding equation and reduction gives:
P =
(K
v
+1)P
sat
A
P
sat
B
K
v
P
sat
A
+ P
sat
B
(B)
For K
v
= 0 P = P
sat
A
For K
v
= ∞ P = P
sat
B
(c) Equations (A) and (B) must yield the same P. Therefore
_
K
l
K
l
+1
_
P
sat
B
+
_
1
K
l
+1
_
P
sat
A
=
(K
v
+1)P
sat
A
P
sat
B
K
v
P
sat
A
+ P
sat
B
Some algebra reduces this to:
K
v
K
l
=
P
sat
B
P
sat
A
(d) As mentioned already, the species (isomers) are chemically similar, and the low pressure favors
ideal-gas behavior.
(e) F = N +2 −π −r = 2 +2 −2 −1 = 1 Thus fixing T should suffice.
708